2014
DOI: 10.1007/s11192-014-1491-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of R&D intensity of countries on the impact of international collaborative research: evidence from Spain

Abstract: A positive influence of international collaboration on the impact of research has been extensively described. This paper delves further into this issue and studies to what extent the type of collaborating country-high, medium or low R&D intensive countryand which country is the leader in the research may influence the impact of the final scientific output. Among 9,961 papers co-authored by scientists from Spain and from another country (bilateral collaboration) during 2008-2009, papers with high R&D intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 34 publications
(40 reference statements)
4
27
0
4
Order By: Relevance
“…This study is the first empirical examination of international contribution and collaboration and its relationship with publishing performance among psychology journals in Brazil. Consistent with Hypothesis 1, as well as recent research ( Adams et al, 2007 ; Bordons et al, 2015 ), is the finding of a higher prevalence of international collaboration among the internationally published journals in the sample. Consistent with Hypothesis 2, as well as recent research ( Packer, 2014 ; Bornmann et al, 2015 ), is the finding of a higher prevalence of non-Brazilian authored contributions among the internationally published journals, in relation to their domestic counterparts.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This study is the first empirical examination of international contribution and collaboration and its relationship with publishing performance among psychology journals in Brazil. Consistent with Hypothesis 1, as well as recent research ( Adams et al, 2007 ; Bordons et al, 2015 ), is the finding of a higher prevalence of international collaboration among the internationally published journals in the sample. Consistent with Hypothesis 2, as well as recent research ( Packer, 2014 ; Bornmann et al, 2015 ), is the finding of a higher prevalence of non-Brazilian authored contributions among the internationally published journals, in relation to their domestic counterparts.…”
Section: Discussionsupporting
confidence: 84%
“…Of these articles, most of them were products of multinational collaboration (i.e., an author from Brazil and authors from at least two other countries). This relationship between international collaboration and strong publishing performance has also been documented in the United Kingdom ( Adams et al, 2007 ), Asia ( Arunachalam and Doss, 2000 ), Spain ( Bordons et al, 2015 ), and Norway ( Aksnes, 2003 ).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Portugal (Baruffaldi and Landoni, 2013), Spain (Bordons et al, 2015;Canibano et al, 2011) and Turkey (Gokbayrak, 2012;Matthews, 2007). Finally, recent simulations also found that declines in international students in the UK as a result of BREXIT would lead to declines in intra-European economic connectivity and sharp declines in GDP (Tijssen et al, 2017;Portes and Forte, 2017).…”
Section: (Ii) Benefits Of Connectivitymentioning
confidence: 99%